Workshop Peningkatan Motivasi Belajar Siswa: Solusi Praktis Bagi Guru-Guru IPA Gugus 1 Muaro Jambi: Penelitian - Desfaur Natalia; Asni Johari; M. Naswir; Dara Mutiara Aswan; M. Erick Sanjaya (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The results of interviews with junior high school teachers in Muaro Jambi Regency revealed that student participation in learning is still lacking and they often ignore assignments given by teachers. They consider science material difficult and uninteresting, which impacts low learning outcomes. This problem is not only caused by internal factors of the students, but also by external factors, namely teachers. Observations show that the learning methods applied are not varied. In addition, teachers' understanding of student learning psychology is still not optimal, thus impacting students' self-confidence and learning motivation. This activity aims to provide practical solutions to MGMP Science teachers in Cluster 1 Muaro Jambi in improving student learning motivation. The implementation method is a participatory workshop involving material presentation, interactive discussions, and practical training on developing learning tools oriented towards increasing learning motivation. The activity evaluation showed a positive response from participants to the activities carried out, with an average score of 3.65 for participant responses, 3.74 for material relevance, 3.91 for usefulness, and 3.91 for clarity of delivery, all in the very good category. These results indicate that the material presented is relevant to teachers' needs and has great potential to be implemented in learning practices.